2009
DOI: 10.1002/adem.200800262
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Ductility on Free Volume in a Cu‐Zr‐Based Metallic Glass

Abstract: Due to the absence of long-range order, bulk metallic glasses (BMGs) exhibit unique properties, such as high strength, high hardness, large elastic limit, good soft magnetic properties, and high corrosion resistance. [1,2] However, there is a fatal weakness that prevents wide application of BMGs: that is almost zero plasticity under tension and limited plasticity under compression. [3][4][5] Therefore, improving the plasticity of metallic glass is currently the subject of extensive study. Recent research has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The smooth region in the tensile fracture surface is corresponding to the critical shear displacement for crack nucleation occurred in shear bands [29][30][31]. This shear displacement is, to some extent, proportional to the plastic deflection [32]. The variations of measured critical shear displacement with the test temperature were also added into Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The smooth region in the tensile fracture surface is corresponding to the critical shear displacement for crack nucleation occurred in shear bands [29][30][31]. This shear displacement is, to some extent, proportional to the plastic deflection [32]. The variations of measured critical shear displacement with the test temperature were also added into Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the cast, annealed, and quenched composite samples were named as sample B1, B2, and B3, respectively. It should be noted that, some experimental results of Cu-Zr-Al BMG in our previous paper [18] were given again at the goal of comparing with the present results of Cu-Zr-Al BMG matrix composites. Figure 1 shows the XRD patterns of the prepared Cu 46 Zr 47 Al 7 alloys.…”
mentioning
confidence: 60%
“…In the early work of Inoue et al [23] and our previous work, [18] it has been suggested that the surface appearance consists of a smooth region and a cores and vein-like pattern region. The former was caused by shear sliding and the latter was caused by subsequent catastrophic failure.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…32) For metallic glasses with different compositions, even through their free volumes are identical, they may have a distinct degree of metallic bonding and dissimilar plasticity. In metallic glass with the same chemical composition but different processing conditions such as quenching rate, 33,34) annealing 35,36) and mechanical pre-deformation, 37,38) a good correlation between the free volume content and the plasticity can usually be found. Contrasting with the findings in this work, it can be concluded that although free volume in metallic glass changes with chemical composition, free volume alone cannot fully describe the influence of the composition on the structure and the mechanical properties of metallic glasses with different compositions.…”
Section: Resultsmentioning
confidence: 99%